1947
DOI: 10.1136/thx.2.4.216
|View full text |Cite
|
Sign up to set email alerts
|

The Results of Thoracoplasty in Pulmonary Tuberculosis

Abstract: The evaluation of thoracoplasty in the treatment of pulmonary tuberculosis depends on so many factors that accurate assessment is difficult. The present survey is submitted with this in mind. It provides, however, some general figures about the fate of the patients and the effects of the operation on their disease.The subject matter of this analysis consists of a follow-up of all cases of thoracoplasty for pulmonary tuberculosis, not complicated by empyema, performed by the writer between 1935 and the middle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1952
1952
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…A recent aptamerbased approach identified the protease-antiprotease balance and tissue remodeling as 2 key pathways that change during tuberculosis treatment, whereas cytokine pathways were not highly represented [47]. All tuberculosis treatments in the preantibiotic era, such as artificial pneumothorax, plombage, and thoracoplasty, centered on cavity collapse, and these had a cure rate of up to 70% [48], demonstrating that macroscopic stabilization of the extracellular matrix can improve host control of M. tuberculosis infection.…”
Section: Discussionmentioning
confidence: 99%
“…A recent aptamerbased approach identified the protease-antiprotease balance and tissue remodeling as 2 key pathways that change during tuberculosis treatment, whereas cytokine pathways were not highly represented [47]. All tuberculosis treatments in the preantibiotic era, such as artificial pneumothorax, plombage, and thoracoplasty, centered on cavity collapse, and these had a cure rate of up to 70% [48], demonstrating that macroscopic stabilization of the extracellular matrix can improve host control of M. tuberculosis infection.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis, in itself, can cause chronic impairment of lung function 12 . Obstruction post‐TPL may result from intramural fibrosis and inflammation of the airways due to previous extensive tuberculous endobronchitis 3,13 , 14 and previous or current smoking. Another contributory factor, however, may be the thoracoplasty itself with increased airway tone and reactivity on the thoracotomy side 15 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that 30 000 TPL were performed in the UK between 1951 and 1960. 2 Although reliable data are available on the early effects of this operation on pulmonary function, 3,4 little data exist on the late sequelae. These studies showed high rates of cure but frequent restrictive sequelae and respiratory failure.…”
Section: Introductionmentioning
confidence: 99%
“…Most appear to have led normal lives in respect of capability for work, marriage, and child bearing, which were sometimes used to judge the success of a thoracoplasty in restoring patients to normality.2 3 The care of most patients with a thoracoplasty is now in the hands of their general practitioners. It is therefore of concern that replies to the questionnaires show that many have persisting symptoms of respiratory disease that they do not report to their general practitioner.…”
Section: Discussionmentioning
confidence: 99%